Effectiveness of Erythropoetin Alpha and Eryhtropoetin Beta in Patients With End-Stage Kidney Disease with Anemia Undergoing Hemodialysis: A Meta-Analysis Study - Sunur, Vincentius William; Sulistio, Timothy; Adisyahputra, Vega; Safira, Vita; Adiwinoto, Ronald Pratama; Setyawan, Yuswanto (Indonesian Journal of Medicine, 2024)
Background and Objectives: One of the causes of anemia in ESRD (End Stage Renal Disease) is due to lack of erythropoietin (EPO) production. The use of short-lived ESA preparations such as Erytrhopoietin alpha and Erytrhopoietin beta still differs in opinion about the effectiveness between the two ESA agents. So the purpose of this study is to review the findings from various studies to provide a better understanding of the effectiveness of the use of ESA. Method The results of the study sought were the effectiveness of erythropoietin alpha and erythropoietin beta which were assessed by the hemoglobin levels in the study. This study uses a meta-analysis design in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Data search using PUBMED, ResearchGate, and ScienceDirect databases Results A total of 458 studies were identified through database sources. After adjusting for inclusion and exclusion criteria, there were 6 studies to be reviewed in a meta-analysis with a total of 220 patients given erythropoietin alpha therapy and 227 patients given erythropoietin beta therapy. The results of the meta-analysis showed that there was no significant difference in the erythropoietin alpha and erythropoietin beta groups after 1 month of therapy (P = 0.20, MD = 0.16, 95% CI [ -0.57, 1.17], I2 = 0% [P = 0.56]), nor after 3 months of therapy (P = 0.19, MD = -0.27, 95% CI [-0.68, 0.13], I2 = 0%, [P = 0.58]) Conclusions There was no significant difference between the effectiveness of erythropoetin alpha and erythropoetin beta in increasing patients' hemoglobin levels. These two ESA agents are effective in increasing hemoglobin levels in ESRD patients.